ملامح النقد الفقهي عند الامام ابن اللباد القيرواني من خلال كتابه الرد على الشافعي - نواصر سعيدة; د/ عبد الرحمان مايدي (جامعة عمار ثليجي الاغواط, 2024)
الملخص بالعربية. حاول هذا البحث تتبع ملامح النقد الفقهي عند اللباد من خلال كتابه الوحيد الرد على الشافعي، ولذلك تناول في البداية ترجمة ابن اللباد وبيان أحوال عصره التي تعطي دارسها المبررات التي شجعت هذا النوع من الدراسات الفقهية التي تتناول الردود على المخالفين خارج المذهب. ثم تطرقت الدراسة للتعريف بكتاب الرد الذي ضمنه المؤلف تفاصيل تلك الردود. وقد ركزت هذه الدراسة على جانبين شكلا أهم الملامح النقدية التي سار عليها ابن اللباد في كتابه، أحدهما: ردوده التي كان محورها خلافات مردها أدلة الاستنباط، والثاني وهو الأكثر ظهورا في الكتاب فيتمثل في نقدهلقضايا تتعلق بالحديث والقول بلا دليل كما زعم ابن اللباد. Abstract in Arabic This research attempted to trace the features of Al-Labbad’sjurisprudential criticism through his only book, which is the response to Al-Shafi’i. Therefore, it initially dealt with Ibn Al-Labbad’s translation and an explanation of the conditions of his time, which give its student the justifications that encouraged this type of jurisprudential studies that deal with responses to opponents outside the doctrine. Then the study addressed the definition of the book of responses, in which the author included details of those responses. The study focused on two aspects that constituted the most important critical features that Ibn al-Labbad followed in his book. First, his responses, the focus of which were disagreements based on deductive evidence. As for the second axis, which is the most extensive, it represented responses that were the basis of criticism in which there were issues related to the hadith